AN ANALYSIS MORAL VALUE IN SONG LYRICS "PRICE TAG" BY JESSIE - Sulistyowati; Veni Evawani Natalia Manalu; Yuli Rohmiyati; Hilman; Raidah Zahra (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study examines the moral values in the song lyrics of Price Tag by Jessie J. . The song critiques the growing focus on materialism and emphasizes the importance of love, happiness, and authenticity in life. The research aims to identify and analyze the moral messages conveyed through the song, using a qualitative approach to explore the lyrics and categorize the moral themes. The analysis reveals that the song advocates for a shift in societal focus—from the pursuit of wealth and material possessions to prioritizing emotional well-being and human connection. The moral values identified in the lyrics include love and affection, bravery, sympathy, and honesty. The findings suggest that the song calls for a shift in focus—from valuing money and possessions to prioritizing emotional well-being, human relationships, and genuine happiness. The most frequent moral value expressed in the song is love and affection, with the lyrics urging listeners to "pay with love" and to prioritize emotional connections over material wealth. In conclusion, Price Tag offers a critique of materialism while encouraging listeners to value love and unity. The study highlights the power of music as a tool for spreading moral messages and inspiring positive change in society, especially in an era where consumerism often overshadows more meaningful pursuits.